The administrative sciences, from the past to the future (by a roundabout route). (March 2014) - Drewry, Gavin
This lecture begins with some preliminary reflections and definitional prescriptions about the nature, content and purpose of the administrative sciences – what they consist of and what purposes they serve. This is followed by a brisk journey through time, starting in the first half of the 18th century, outlining the development of the administrative sciences, using a road traffic metaphor to describe how the volume and complexity of the subject has grown in response to industrialization and globalization. The lecture draws in particular on the rather peculiar pattern of development in the author's own country – the UK – as a basis for some more general observations. The 'road' that is followed is not a straight one and the author has been very selective in the landmarks that he has chosen to point out along the way. The latter part of the lecture takes stock of where this journey has taken us and offers some tentative speculations about where the road might lead in the future. It concludes with some thoughts about how the diversity and volume of intellectual traffic that constitutes the administrative sciences might be managed – with special reference to the role of national and international institutes of public administration.